A low-cost green technology for recovering lead paste and lead-alloy grid materials for spent lead acid batteries. (3rd April 2017) - Kumar, R. Vasant
ABSTRACT: A new method, currently under industrial trial, consists in dissolving the hard-to-recover lead-bearing active components of battery paste in an aqueous solution of carboxylic acids, derived from plants, and precipitating the lead as organic crystal plates. The lead organic material is self-combusting, generating leady oxide as desired for direct new battery paste preparation. The organics, embodied in the precursor, serve as the fuel by combustion to aid calcination. The lead grids are refined separately using heat from the first process. The use of acids from plants which is produced using a renewable stock, not only as a reagent but also as source of energy, will result in a very low-carbon footprint. Since economy of scale is not a limiting factor, such a technology will offer the vision for nucleating/retrofitting many small-scale lead battery operations in rural industry in rapidly growing economies.